Performance of coated- and uncoated-carbide tools when drilling titanium alloy—Ti–6Al4V - Sharif, Safian (Elsevier B.V., 2007)
In this paper, the performance of uncoated-WC/Co and alloy—Ti–6Al4V coated-carbide twist drills were investigated when drilling titanium alloy, Ti–6Al4V. The effect of cutting speed on tool wear, tool life and surface finish of the hole when drilling using coolant were reported. Results showed that non-uniform flank wear, chipping and catastrophic failure were the dominant modes of tool failure for both coated- and uncoated-drills. It was found that at all cutting speeds tested, TiAlN-coated-drill significantly outperformed uncoated-drill in terms of tool life and surface finish. The highest tool life recorded for TiAlN-coated-drill was 7.8 min after drilling the 25th hole at the lowest cutting speed of 25 m/min and feed of 0.06 mm/rev. The effect of cutting speed on the performance of the uncoated-carbide drill was less significant at all cutting speed tested when all the drills failed prematurely with recorded tool lives of less than 1 min.